Menentukan Panjang Pipa Terpendek Untuk Pemasangan Jaringan Pipa Pdam Di Kecamatan Koto Tangah Kota Padang - Iswan Rina; Nurweni Putri (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
The writting is shown by the completion of the PDAM data by determining the shortest lenght of the PDAM data, in other words looking for the shortest lenght of the three model.